Henoch-Schönlein purpura in childhood: treatment of rapidly progressive glomerulonephritis with immunosuppressive anticoagulant therapy - Mocan, Hilal; Murphy, Anna V.; Beattie, T. James; Gibson, A. Angus (The Turkish Journal of Pediatrics, 1988)
Ten patients with rapidly progressive glomerulonephritis (RPGN) were treated with prednisolone, azathioprine or cyclophosphamide, dipyridamole, heparin and/or warfarin for periods of 1.7 weeks to 144 weeks with a mean period of 44 weeks. Three patients responded well, their mean glomerular filtration rate before treatment being 31.7 ml/min/1.73 m² to a mean of 111 ml/min/1.73 m² after treatment, the follow-up period being 45.3 months. Three patients had a partial response, showing a temporary rise in GFR and four patients had no response. Our observations suggested that this combined therapy has a place in patients with RPGN, especially in those patients where at the start of the treatment GFR is more than 20 ml·min/1.73 m², oliguria is absent and where crescents on renal biopsy are predominantly cellular. The incidence of side effects was high and it is necessary that the therapy be used with caution.
Keywords: Henoch-Schönlein purpura; rapidly progressing glomerulonephritis; immunosuppressive therapy; anticoagulant therapy; quadruple therapy